2019
DOI: 10.1021/acs.analchem.8b03828
|View full text |Cite
|
Sign up to set email alerts
|

The Plethora of Angiotensin-Converting Enzyme-Processed Peptides in Mouse Plasma

Abstract: Angiotensin-converting enzyme (ACE) converts angiotensin I into the potent vasoconstrictor angiotensin II, which regulates blood pressure. However, ACE activity is also essential for other physiological functions, presumably through processing of peptides unrelated to angiotensin. The goal of this study was to identify novel natural substrates and products of ACE through a series of mass-spectrometric experiments. This included comparing the ACE-treated and untreated plasma peptidomes of ACE-knockout (KO) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 76 publications
1
30
0
Order By: Relevance
“…The finding of high aldosterone in conjunction with suppressed angiotensin II formation in some dogs in this study suggests that ABT is occurring independent of angiotensin II. A multitude of peptides serve as substrates for ACE, and the accumulation of these peptides as a result of ACE‐inhibition could be contributing to the formation of aldosterone through other pathways . These findings are important because they demonstrate the efficacy of enalapril in suppressing angiotensin II formation, but also show ABT and indicate that multimodal RAAS suppression may be indicated to address modulation of other pathways by ACE‐inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of high aldosterone in conjunction with suppressed angiotensin II formation in some dogs in this study suggests that ABT is occurring independent of angiotensin II. A multitude of peptides serve as substrates for ACE, and the accumulation of these peptides as a result of ACE‐inhibition could be contributing to the formation of aldosterone through other pathways . These findings are important because they demonstrate the efficacy of enalapril in suppressing angiotensin II formation, but also show ABT and indicate that multimodal RAAS suppression may be indicated to address modulation of other pathways by ACE‐inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of peptides serve as substrates for ACE, and the accumulation of these peptides as a result of ACE-inhibition could be contributing to the formation of aldosterone through other pathways. 23 and inhibition of angiotensin II formation or binding (ACE-inhibitors or angiotensin receptor blockers, respectively) is often necessary to provide comprehensive RAAS inhibition. 18,21,24 Additional study is required to elucidate other pathways that may be impacted by RAAS inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The centrality of sACE in regulating the levels of these diverse peptides has made it an attractive drug target for conditions such as hypertension, kidney disease, cardiovascular disease, fibrosis and Alzheimer’s disease. The full extent of this protein’s influence on human health and disease is, however, still unknown, as was emphasised by a recent study which identified more than 240 ACE-regulated peptides in mouse plasma [ 19 ]. Even the ‘traditional’ blood pressure-regulating function of sACE is more complex than originally thought, with cross-talk occurring between the RAAS, natriuretic peptide system (NPS), kallikrein–kinin system (KKS) and the counterregulatory Mas axis of the RAAS [ 20 ].…”
Section: Biochemical Properties Of Vertebrate Acementioning
confidence: 99%
“…In addition to Ang I, peptides that have been identified as substrates for these and potentially other roles include N-acetyl-Ser-Asp-Lys-Pro (AcSDKP), substance P, enkephalins, luteinising hormone-releasing hormone, kinins, the amyloid-beta peptide (Ab), neurotensin and formyl-Met-Leu-Phe [16][17][18][19][20][21]. A recent study which used mass spectrometry to study ACE activity in mouse plasma identified more than 240 potential substrates or products of ACE, demonstrating the vast promiscuity of this enzyme [22]. Furthermore, ACE has been implicated in the immune response through cleavage of Ang I as well as an unknown substrate [23].…”
Section: Introductionmentioning
confidence: 99%